Evaluation of the Therapeutic Pattern and Pharmaco-Utilization in Hypercholesterolemic Patients Treated with Statins: A Retrospective Study on Italian Real-World Data - Perrone V; Giacomini E; Sangiorgi D; Andretta M; Bartolini F; Lupi A; Ferrante F; Palcic S; Re D; Degli Esposti L (Dove Medical Press, 2022)
Valentina Perrone,1 Elisa Giacomini,1 Diego Sangiorgi,1 Margherita Andretta,2 Fausto Bartolini,3 Alessandro Lupi,4 Fulvio Ferrante,5 Stefano Palcic,6 Davide Re,7 Luca Degli Esposti1 1CliCon S.r.l. Società Benefit - Health, Economics & Outcome Research, Bologna, Italy; 2UOC Assistenza Farmaceutica Territoriale, Azienda ULSS 8 Berica, Vicenza, Italy; 3Dipartimento Farmaceutico-USL Umbria 2, Terni, Italy; 4ASL VCO, Omegna (VB), Italy; 5ASL Frosinone, Frosinone, Italy; 6Azienda Sanitaria Universitaria Integrata Giuliano-Isontina (ASUGI), Trieste, Italy; 7U.O.C. Servizio Assistenza Farmaceutica Territoriale, ASL Teramo, Teramo, ItalyCorrespondence: Valentina Perrone, CliCon S.r.l. Società Benefit - Health, Economics & Outcome Research, Via Murri 9, Bologna, 40137, Italy, Tel +39 3450316494, Email valentina.perrone@clicon.itPurpose: The study aimed to analyze, in hypercholesterolemic patients under statin medication, patient characteristics and their lipid profile at baseline, the therapeutic pathway, and the pharmaco-utilization, using real-world data in Italy.Patients and Methods: A retrospective study was conducted using administrative databases of a sample of entities covering 6.5 million health-assisted individuals. Between January 2010 and June 2019, patients with non-familial hypercholesterolemia (nFH) were identified by 1) ≥ 1 low-density lipoprotein cholesterol (LDL-C) measurement (LDL-C assessment date was the index-date) and 2) statin prescription during 6 months before the index-date (pharmaco-utilization period). FH patients were defined by LDL-C evaluation, statin treatment during the pharmaco-utilization period, and a score ≥ 6 according to the Dutch Lipid Clinic Network criteria. nFH patients were divided into four exclusive cohorts based on CV-risk class: 1) with previous CV disease (CVD); 2) with diabetes mellitus; 3) with mixed-dyslipidemia diagnosis; 4) in primary-prevention. Based on LDL-C index values, patient was defined with LDL-C "controlled" if its levels were ≤ 70mg/dl (CVD), ≤ 100mg/dl (diabetes, FH), ≤ 130mg/dl (mixed-dyslipidemia, primary-prevention).Results: Overall 164,161 nFH patients were included (mean age 72 years, 51% male); of these, 46,782 (28.5%) were CVD (mean age 74 years, 66% male), 34,803 (21.2%) were diabetic (mean age 72 years, 51% male), 1617 (1%) were with mixed-dyslipidemia (mean age 71 years, 48% male) and 80,959 (49.3%) were in primary-prevention (mean age 71 years, 42% male). The proportion of nFH patients with controlled LDL-C was 41.2% for CVD, 73.6% for diabetic, 80.7% for mixed-dyslipidemia, and 79.5% for primary-prevention patients; 49% of nFH patients were adherent to therapy. Overall, 1287 FH patients (mean age 64 years, 42% male) were included; in 39.2% of the patients, LDL-C was controlled, and 44% of the patients were adherent to therapy.Conclusion: The results of this study highlighted non-optimal therapeutic management of hypercholesterolemic patients in Italian clinical practice, with a notable quote of patients non-adherent to therapy.Keywords: lipid-lowering agents, pharmacoutilization, real-world evidence, clinical practice